Re-examining The American Dream: A Postcolonial Study of Laila Lalami`s The Other Americans (2019) - Sadeki ,Ayoub; SELT, Djihad Afaf (Faculty of Letters and Foreign Languages Department of English, 2023)
America has been promoted as the land of dreams and opportunities, people from different parts of the world choose the path of the unknown destiny to achieve success and fortune through immigration, crossing borders, seas, and oceans chasing their passion. This research re-examines the American dream through the novel Laila Lalami’s The Other American (2019). This thesis adopted a historical and postcolonial approach, along with qualitative, descriptive, and analytical methods. These latter helped to look into the truthfulness of the American dream and how various types of immigrants handle it in a diasporic community. As a consequence, problems that second-generation immigrants face have originated from their ex-colonized countries with their political instability which pushed them to flee and be exiled in someone’s else society in search of an opportunity that was not fulfilled, much like the work of Lalami that investigates the American dream as a failure not as a success